Diseño de la imagen institucional del gobierno autónomo descentralizado del cantón Salcedo, para facilitar la comunicación visual ante la sociedad Salcedense en el período 2014 - Balarezo Vasco, Diego Miguel (2014)
This research is focused to contribute with an institutional image in Salcedo’s GAD, in order to give a solution to several promotion and diffusion problems by the advertising system, expiring with the planned scientific parameters and methodology are based too. The following proposal is based on a previous researching at the Salcedo’s GAD, for this reason the design of the institutional image preserves his institutional features, which are established by graphical designing adequately and that are reflected in each of the graphical elements.